Gamete interactions require transmembranous immunoglobulin-like proteins with conserved roles during evolution. Issue 3 (2nd July 2016) - Nishimura, Hitoshi; L'Hernault, Steven W.
ABSTRACT: C. elegans spe-9 class genes are male germline-enriched in their expression and indispensable during sperm-oocyte fusion. Identification of mammalian orthologs that exhibit similar functions to these C. elegans genes has been a challenge. The mouse Izumo1 gene encodes a sperm-specific, immunoglobulin (Ig)-like transmembrane (TM) protein that is required for gamete fusion. We recently identified the C. elegans spe-45 gene, which shows male germline-enriched expression and encodes an Ig-like TM protein. spe-45 mutant worms produced otherwise normal spermatozoa that cannot fuse with oocytes, causing essentially the same phenotype as that seen in the Izumo1 -knockout mice. By counting the number of self-sperm in the spermatheca of spe-45 hermaphrodites, it was found that this gene might be involved in sperm guidance from the uterus into the spermatheca, as well as gamete fusion. Moreover, we discovered that SPE-45 and IZUMO1 share certain functions for gamete fusion, which are presumably related to binding with cis - and/or trans -partners. Intriguingly, various organisms have Ig-like TM proteins that act during gamete interactions, indicating the wide-spread utility of Ig-like domains during fertilization.